DISTRIBUSI SPASIAL ZOOPLANKTON DI DANAU LINDU, DAN BEBERAPA FAKTOR YANG MEMPENGARUHI KELIMPAHANNYA - lukman lukman (Jurnal Teknologi Lingkungan, 2005)
Lake Lindu is located in conservation area, the Lore Kalamanta National Park, and still on natural condition. Therefore, it is interesting to recognize their biological condition, especially zooplankton existence. It was observed the zooplankton spatial distribution on March 2001 and evaluated the factors which influenced to their abundance. Four sampling station at rivers, inlet of the lake, five in lake waters body at 0 m; 3 m , 5 m, and 10 m water depth were studied. Supporting data, namely organic content on COD(Chemical Oxygen Demand) parameter was measured on same location, for a while phytoplankton and heterotrophyc bacteria data from secondary data. There were five genus zooplankton, namely Ceriodaphnia (Cladocera), Diaptomus, Cyclops (Copepoda), Brachionus and Filinia (Rotifera). It was not found zooplankton at rivers, therefore average of abundance in lake water body ranged 37 - 376 ind.l-1, and based of depth stratum their abundance show to maximize at three meters depth. Zooplankton abundance seem correlate support factors quadratically, positively to COD and abundance of heterothrophyc bacteria, but negatively to phytoplankton abundance.